Geometric phase for timelike spherical normal magnetic charged particles optical ferromagnetic model - Korpinar, Talat; Korpinar, Zeliha; İnç, Mustafa; Baleanu, Dumitru (Taylor & Francis Ltd, 2020)
We introduce the theory of optical spherical Heisenberg ferromagnetic spin of timelike spherical normal magnetic flows of particles by the spherical frame in de Sitter space. Also, the concept of timelike spherical normal magnetic particles is investigated, which may have evolution equations. Afterward, we reveal new relationships with some integrability conditions for timelike spherical normal magnetic flows in de-Sitter space. In addition, we obtain total phases for spherical normal magnetic flows. We also acquire perturbed solutions of the nonlinear Schrodinger's equation that governs the propagation of solitons in de-Sitter space S-1(2). Finally, we provide some numerical simulations to supplement the analytical outcomes.
Keywords: Moving space curves; optical fibre; geometric phase; evolution equations; travelling wave hypothesis; Heisenberg ferromagnetic model